Ectopic expression of Triticum polonicum VRT-A2 underlies elongated glumes and grains in hexaploid wheat in a dosage-dependent manner. Issue 7 (1st May 2021) - Adamski, Nikolai M.; Simmonds, James; Brinton, Jemima F.; Backhaus, Anna E.; Chen, Yi; Smedley, Mark; Hayta, Sadiye; Florio, Tobin; Crane, Pamela; Scott, Peter; Pieri, Alice; Hall, Olyvia; et al.
Abstract: Flower development is an important determinant of grain yield in crops. In wheat ( Triticum spp.), natural variation for the size of spikelet and floral organs is particularly evident in Triticum turgidum ssp. polonicum (also termed Triticum polonicum ), a tetraploid subspecies of wheat with long glumes, lemmas, and grains. Using map-based cloning, we identified VEGETATIVE TO REPRODUCTIVE TRANSITION 2 ( VRT2 ), which encodes a MADS-box transcription factor belonging to the SHORT VEGETATIVE PHASE family, as the gene underlying the T. polonicum long-glume ( P1 ) locus. The causal P1 mutation is a sequence rearrangement in intron-1 that results in ectopic expression of the T. polonicum VRT-A2 allele. Based on allelic variation studies, we propose that the intron-1 mutation in VRT-A2 is the unique T. polonicum subspecies-defining polymorphism, which was later introduced into hexaploid wheat via natural hybridizations. Near-isogenic lines differing for the P1 locus revealed a gradient effect of P1 across spikelets and within florets. Transgenic lines of hexaploid wheat carrying the T. polonicum VRT-A2 allele show that expression levels of VRT-A2 are highly correlated with spike, glume, grain, and floral organ length. These results highlight how changes in expression profiles, through variation in cis-regulation, can affect agronomic traits in a dosage-dependent manner in polyploid crops. Abstract : An intron-1 rearrangement in the MADS-box transcription factor gene VRT-A2 leads to its misexpression and defines the long-glume phenotype of Polish wheat ( T. polonicum ).